School Leaders in Kazakhstan: Perspectives, Roles and Challenges - Nurmukhanova, Dana (Journal of Education in Black Sea Region, 2020)
School leadership is back to fashion and became the major concern for many pieces of research. Expectations from schools and school leaders are changing along with time and society demands. Countries care about the future and its competitive capacity in a global arena, hence, one of the strategic directions is to invest in education. Moreover, current tendencies require reconsidering the activities of educational leaders at all levels. This paper aims at exploring the current situation of school leadership and school leaders in general and research the perspectives, roles, and challenges they face nowadays. The paper also considers international perspectives on school leadership as well as the context of Kazakhstan. The study discusses the variety of leadership roles and challenges the school leaders confront aiming at school development. The findings include the overview of school management systems and existing practices of school development in Kazakhstan. Nevertheless, there is a number of challenges in understanding the concept of school leader and the roles due to the lack of consistent research on effective practices. The paper reveals a number of inconsistencies in terms of the lack of differentiation between the roles, characteristics, and responsibilities of school leaders. The research provides recommendations on conducting larger-scale research to enable the complete picture of school leadership in Kazakhstan.